Multidimensional Impact of Overweight on Quality of Life of Children and Adolescents: A Scoping Review - Iin Utami Yasrianti Lamukara; Nur Setiawati Dewi; Rita Hadi Widyastuti (Indonesian Journal of Global Health Research, 2025)
Overweight in adolescents is a global health issue that has shown a significant increase in recent decades. This condition has a multidimensional impact, particularly on the physical, psychological, social aspects, and overall quality of life of adolescents. Children and adolescents who are overweight often experience body shaming, social stigma, decreased self-esteem, and social isolation, all of which can contribute to a lower quality of life. Although numerous studies have explored the relationship between being overweight and quality of life, most have focused only on physical or psychological dimensions. Many of the existing studies examine just one or two aspects of quality of life and lack a comprehensive consideration of cultural factors, developmental age, and social interactions. Objective to comprehensively review the scientific literature that examines the impact of overweight on the quality of life among adolescents. This study employed a scoping review approach based on the PRISMA-ScR guidelines. Literature searches were conducted through three databases: Scopus, PubMed, and ScienceDirect, using the keywords "Overweight," "Adolescents," and "Quality of Life." The selected articles were published within the last three years (2023–2025) and met the inclusion criteria, including being written in English, open access, and relevant to the topic. A total of 15 articles were selected from an initial search result of 18,441 records. The article selection involved a multi-stage screening process, including title and abstract screening, full-text review, and assessment using inclusion and exclusion criteria. Each article was then analyzed thematically to identify patterns related to the impact of overweight on adolescents' quality of life. These studies employed qualitative and quantitative approaches, including multivariate analysis, logistic models, as well as mediation and moderation analyses. Most of the articles reported that overweight has a negative impact on adolescents’ quality of life, particularly in the physical, psychological, social, and academic functioning domains. Overweight in adolescents has a significant impact on various aspects of quality of life. These findings highlight the importance of developing multidimensional interventions that not only address physical aspects but also take into account psychosocial factors and the adolescent’s environment.